2002
DOI: 10.1677/joe.0.1750705
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid effects on chondrogenesis, differentiation and apoptosis in the murine ATDC5 chondrocyte cell line

Abstract: Glucocorticoids (GC) are used extensively in children and may cause growth retardation, which is in part due to the direct effects of GC on the growth plate. We characterised the ATDC5 chondrocyte cell line, which mimics the in vivo process of longitudinal bone growth, to examine the effects of dexamethasone (Dex) and prednisolone (Pred) during two key time points in the chondrocyte life cyclechondrogenesis and terminal differentiation. Additionally, we studied the potential for recovery following Dex exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…Cells were differentiated at 37°C in a humidified atmosphere containing 5% CO 2 for 8 -15 days, and Dex (final concentration 10 Ϫ6 M) was added to the cells at the indicated times. We and others have previously shown that, from 8 days of differentiation, ATDC5 cells express the chondrocyte marker gene collagen type II, and by day 15 the cells display a terminally differentiating phenotype with increased levels of collagen type X and aggrecan expression and the formation of nodules (49,16). To test lipocalin 2 expression following exposure to other antiproliferative treatments, ATDC5 cells were cultured in the presence of ceramide (40 M), TNF␣ (10 ng/ml), or serum-free medium (SFM) for 48 h. The protein synthesis blocker cycloheximide (CHX; 8 g/ml), and the GC receptor antagonist RU-486 (10 Ϫ5 M) were added to ATDC5 cells to investigate the mechanisms involved in Dex-induced lipocalin 2 expression.…”
Section: Methodsmentioning
confidence: 82%
“…Cells were differentiated at 37°C in a humidified atmosphere containing 5% CO 2 for 8 -15 days, and Dex (final concentration 10 Ϫ6 M) was added to the cells at the indicated times. We and others have previously shown that, from 8 days of differentiation, ATDC5 cells express the chondrocyte marker gene collagen type II, and by day 15 the cells display a terminally differentiating phenotype with increased levels of collagen type X and aggrecan expression and the formation of nodules (49,16). To test lipocalin 2 expression following exposure to other antiproliferative treatments, ATDC5 cells were cultured in the presence of ceramide (40 M), TNF␣ (10 ng/ml), or serum-free medium (SFM) for 48 h. The protein synthesis blocker cycloheximide (CHX; 8 g/ml), and the GC receptor antagonist RU-486 (10 Ϫ5 M) were added to ATDC5 cells to investigate the mechanisms involved in Dex-induced lipocalin 2 expression.…”
Section: Methodsmentioning
confidence: 82%
“…To mechanistically investigate the role of HPSE in endochondral bone formation, we used the well accepted ATDC5 cell in vitro model system, because it permits study of both chondrogenesis and osteogenesis within the same cell culture system [76]. ATDC5 also can mineralize spontaneously without the addition of an exogenous substrate such as β-glycerophosphate [77].…”
Section: Discussionmentioning
confidence: 99%
“…(43) The bones were washed in PBS (3 Â 15 minutes) and unbound thymidine extracted using 5% TCA (2 Â 30 minutes). (45,46) Experiments requiring serum deprivation and GH or IGF-1 challenge were treated as described above for primary cells.…”
Section: Metatarsal [ 3 H]-thymidine Proliferation Assaymentioning
confidence: 99%